(untitled) (Journal of the College of Education for Women, 2019)
Abstract:Taghlib tribe had an important part in the history of the first century ofhijra. She managed to get the best social, economic and political basis in theArab- Islamic state. In this basis Taghlib was the best Dhimies in the Islamicstate. This tribe refused to be among the people of the book, and to be fromthe people of dhima. That tribe refused to pay the Jizya and Khraj, butaccepted to pay double Sadaqa in stead of Jizya and Khraj, so in that casemany Muslims become angry.Although their Christianity was naïve and simple, Taghlib hold it until theend of the third century A.H. Taghlib did so because her people wanted tokeep their good relation with the Byzantine. Taghlib thought that theChristianity was a good way to protect their independence and the unity oftheir existence. The Christianity differentiates them from the other Arab tribesin the Arabian Peninsula, and the people of the book.The prophet treated them with a good policy so did the rightly guidedcaliphs, Omar wrote a good peace treaty for them. In this peace treaty herecognized their religion and personality, so did Othman and Ali.Taghlib entered Avery hard wars with the Qaisit Arab - tribes in the Jaziraalfuratiya.These wars were for economics, politics and socialist reasons.Taghlib had got the help of her Islamic branches in athirbegan, kufa andBasra. This means that the tribal solidarity was joining the Muslims Arab tribeswith the Christian Arab- tribes.